Serwicyzacja ekonomicznych funkcji gospodarstwa domowego jako przedmiot badania statystycznego - Romanow, Halina (Wydział Prawa i Administracji UAM, 1972)
Several changes in the household activities take place together with the economic development of the community. Here belongs the changeover to services in the field of economic functions of a household i.e. some of the functions are taken over by servicing institutions. The article presents the changeover to services as a complex statistical quality characteristic of the units forming the housekeeping population. Among the factors differentiating the level of the process a category for itself is the demographic and socio-economic characteristics of households. To formulate a functional relationship between the factors and the level of serviceability a model of multiple linear regression is proposed in which the illustrated variable has the form of probability and the illustrating variables are the zero-one variables defining the character of the household.
Changeover to Services in the Field of Economic Functions of Households as a Subject of Statistical Research